DEVELOPMENT OF THE LADDER SNAKE GAME MEDIA IN ARABIC LEARNING/ PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA DALAM PEMBELAJARAN BAHASA ARAB - Baroroh, R Umi; Mardliyyah, Aisyam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
This research was conducted to develop a snake ladder game media for learning Arabic and describes its influence on student learning outcomes, with the subject of class V MI Ma'arif Bego Sleman Yogyakarta. This research belongs to the Research and Development (R D) category. The instruments used in this study were observation, interviews, documentation, material questionnaires, media expert questionnaires, peer reviewer questionnaires, and student responses. The data analysis technique in this study used descriptive analysis in percentage. The results showed that: 1) snakes and ladders playing media for learning Arabic the criteria for